(3eSGdc GdCHUGQ aj eeGdc GdCeUGQs - (3CMeO Hf jMji Hf aVd Gddg GdbQTj GdYOhj GdYeQj, TgGH GdOjf,J (B749 (3g` s
(3ChdgG (B:s
(3PcQ Jeje Hf GdeYR s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B268 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B204s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B141 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B102 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeYGQa GdYGeIs